Loss of ARHGAP15 affects the directional control of migrating interneurons in the embryonic cortex and increases susceptibility to epilepsy - Liaci, Carla; Camera, Mattia; Zamboni, Valentina; Sarò, Gabriella; Ammoni, Alessandra; Parmigiani, Elena; Ponzoni, Luisa; Hidisoglu, Enis; Chiantia, Giuseppe; Marcantoni, Andrea; Giustetto, Maurizio; Tomagra, Giulia; et al. (Frontiers in Cell and Developmental Biology, 2022)
GTPases of the Rho family are components of signaling pathways linking extracellular signals to the control of cytoskeleton dynamics. Among these, RAC1 plays key roles during brain development, ranging from neuronal migration to neuritogenesis, synaptogenesis, and plasticity. RAC1 activity is positively and negatively controlled by guanine nucleotide exchange factors (GEFs), guanosine nucleotide dissociation inhibitors (GDIs), and GTPase-activating proteins (GAPs), but the specific role of each regulator in vivo is poorly known. ARHGAP15 is a RAC1-specific GAP expressed during development in a fraction of migrating cortical interneurons (CINs) and in the majority of adult CINs. During development, loss of ARHGAP15 causes altered directionality of the leading process of tangentially migrating CINs, along with altered morphology in vitro. Likewise, time-lapse imaging of embryonic CINs revealed a poorly coordinated directional control during radial migration, possibly due to a hyper-exploratory behavior. In the adult cortex, the observed defects lead to subtle alteration in the distribution of CALB2-, SST-, and VIP-positive interneurons within the cortex. Adult Arhgap15-knock-out mice also show reduced CINs intrinsic excitability, spontaneous subclinical seizures, and increased susceptibility to the pro-epileptic drug pilocarpine. These results indicate that ARHGAP15 imposes a fine negative regulation on RAC1 that is required for morphological maturation and directional control during CIN migration, with consequences on their laminar distribution and inhibitory function.